Empirical evidence on good governance in public tertiary institutions of Nigeria: The effects on entrepreneurship and performance - Saidu, Alhaji Adamu; Din, Badariah; Kling, Zainal (Society of Scientific Research and Education (SSRE), 2016)
The idea of entrepreneurship in the public sector was a paradox from different scholars, previous studies on entrepreneurship hubs around private sector organizations until when public administration began to experience a shift of paradigm to a new public Management then public entrepreneurship start to gain more recognition. The financial crisis and economic meltdown prompt other countries in the world and Africa to join western countries in fine tuning other means of financing public services. The Nigerian public sector was observed to be ineffective due to inadequate fund and economic mismanagement. The Nigerian government understands the importance of tertiary institution in the provision of education and device different policies and legislation to improve its performance yet little success was recorded. Government alone cannot handle education; therefore the needs of entrepreneurship in public tertiary institutions became Imperative. The primary concern of this study was to examine the effects of good governance on entrepreneurship and organizational performance of the public tertiary Institution. This study uses the primary source and obtained data from 160 academic administrators, The Partial lease square PLS (SEM) was used for the analysis. The finding proves good governance was instrumental to entrepreneurship and effective performance of the public tertiary institution in Nigeria and contributes in terms of the theoretical and practical implications.